Study protocol: hypnosis versus standard care for shoulder dislocation reduction in the emergency department – a multicentre, randomised, controlled study protocol - Marion Douplat; Guillaume Durand; Coraline Hingray; Christophe Goetz; Nadia Ouamara; Sandra Marchionni; Marine Demarquet; Marion Tinelli; Nazmine Guler; Philippe Aim; Lauriane Cipolat; Emmanuelle Seris; et al. (BMJ Open)
Introduction Anterior shoulder dislocation is a common reason for consultation at the emergency department (ED). Hypnosis could be a safe and effective alternative therapy for pain relief during shoulder dislocation reduction but nowadays, evidence is not sufficient. The main objective of this study is to show that reduction under hypnosis is associated with a decrease in the use of analgesic compared with usual care.Methods and analysis We will conduct an interventional, controlled, multicentre, randomised study. A total of 44 patients with shoulder dislocation will be randomised in two groups: the hypnosis group (N=22) and the usual care group (N=22). The primary endpoint will be the comparison of morphine equivalent analgesic consumption during a shoulder dislocation reduction manoeuvre. Secondary endpoints will include haemodynamic parameters monitoring, patient and practitioner satisfaction using a Likert scale, use of coanalgesic or sedative drugs, number of reduction attempts and time spent at ED. Adverse events will be recorded. Statistical analysis will include parametric tests, multivariate linear regression and descriptive statistics.Ethics and dissemination This study has received ethics approval from the Comité de Protection des Personnes of Sud-Est IV on 03/11/2021 (ANSM informed on 19 November 2021). The results will be published in scientific articles and communicated in national and international conferences.Trial registration number ClinicalTrial.gov: NCT04992598; National Clinical trial no ID RCB : 2021-A01382-39